Sero-prevalence of Taenia spp. cysticercosis in rural and urban smallholder pig production settings in Uganda - Kungu, Joseph M.; Dione, Michel M.; Ejobi, F.; Harrison, L.J.S.; Poole, Elizabeth J.; Pezo, Danilo A.; Grace, Delia (Elsevier, 2017)
The pork tapeworm, Taenia solium, is prevalent in Uganda although the prevalence has not been determined in all areas of the country. A cross-sectional study, to determine the sero-prevalence of the parasite in pigs kept under rural and urban production settings, was carried out in three Ugandan districts, Masaka, Mukono and Kamuli. Serum samples from 1185 pigs were tested for the presence of T. solium cysticercosis antigen using the HP10 antigen-ELISA (Ag-ELISA) and the ApDia Ag-ELISA assays. Using parallel interpretation of the two tests showed lower levels of observed prevalence of T. solium in rural production settings (10.8%) compared to urban (17.1%). Additionally, Maximum Likelihood Estimation for evaluating assays in the absence of a gold standard, using TAGS on the R platform, estimated the true sero-prevalence to be lower in rural production setting, 0.0% [0.0–3.2%; 95% confidence interval (CI)] than in urban production setting, 12.3% (4.2–77.5% CI). When the sensitivity/specificity (Se/Sp) of the assays were estimated, assuming conditional independence of the tests, HP10 Ag-ELISA was more sensitive and specific [(Se = 53.9%; 10.1–100% CI), (Sp = 97.0%; 95.9-100% CI)] than the ApDia assay [(Se = 20.2%; 1.5–47.7% CI), (Sp = 92.2%; 90.5–93.9% CI)]. Subject to parasitological verification, these results indicate there may be a need to implement appropriate control measures for T. solium in the study areas.